Infectious complications and conservative treatment of totally implantable venous access devices in children with cancer - Yazıcı, Nalan; Akyüz, Canan; Yalçın, Bilgehan; Varan, Ali; Kutluk, Tezer; Büyükpamukçu, Münevver (The Turkish Journal of Pediatrics, 2013)
Besides their complications, totally implantable venous access devices (TIVADs) increase the quality of life in children with cancer. The aim of this study was analysis of infectious complications and results of conservative management in TIVADs. Three hundred and one catheters were implanted in 283 patients between February 1991 and January 2005. Infectious complications were analyzed retrospectively. Cumulative duration of implantation was 153,757 days. In 140 devices (46.5%), no complication was detected. Total rate of infection was 1.96/1000 catheter days. Types of infections were as follows: catheterrelated bloodstream infections: 190; catheter-related systemic infections: 74; pocket infections: 19, exit site infections: 14; and tunnel infections: 5. Staphylococcus epidermidis and non-albicans candida were the most common isolations. During follow-up, a total of 119 catheters had been removed. Most of them were due to infection (n=42). In conclusion, TIVADs are important in children with cancer who need prolonged intravenous access, so they should be used carefully and managed conservatively in case of complications.